Changes in shear wave splitting before the 2010 Eyjafjallajokull eruption in Iceland - Liu, Sha; Crampin, Stuart; Luckett, Richard; Yang, Jiansi (Geophysical Journal International, 2014)
We use shear wave splitting (SWS) above microearthquakes to monitor stress variations before the 2010 March and April flank and summit eruptions of Eyjafjallajökull volcano in Iceland. SWS time delays before Eyjafjallajökull show characteristic variations similar to those seen before earthquakes. The time delays display a nearly linear increase before the eruption, an abrupt change of slope and a rapid nearly linear decrease until the flank eruption begins. Similar variations before earthquakes are interpreted as stress-accumulation increases, and stress-relaxation decreases as microcracks coalesce onto the eventual fault plane. The changes in SWS before Eyjafjallajökull are interpreted as a similar stress-accumulation increase, as magma penetrates the crust, and stress-relaxation decrease as microcracks coalesce onto the magma conduit prior to magma release. We suggest that the remarkable similarity between stress changes before eruption and earthquake is strong evidence for the New Geophysics of a critically microcracked crust.